PENGARUH AGENCY COST, PROFITABILITAS, DAN DEBT TO EQUITY RATIO (DER) TERHADAP KEBIJAKAN DIVIDEN (Studi pada Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Yolandha Ayudya Fitriana; Leny Suzan (Yayasan Akrab Pekanbaru, 2018)
This study aims to know the influence of Agency Cost, Profitability, and Debt to Equity Ratio (DER) toward Dividend Policy proxied by Dividend Payout Ratio (DPR) at basic industries and chemicals sector listed on the Indonesian Stock Exchange (BEI) in the period of 2012-2016. The data used in this study was obtained from financial statement data. The population in this study are basic industries and chemical sectors listed on Indonesian Stock Exchange. The sample selection technique used is purposive sampling and acquired 11 companies in basic industries and chemical sectors during 2012-2016 studying period. The methods of data analysis in this study is panel data regression analysis using Eviews Software 9.0. The results of this study shows that the simultaneous of Agency Cost, Profitability, and Debt to Equity Ratio (DER) have a significant effect on the dividend policy. Whereas partially, the Agency Cost has negative effect on dividend policy, meanwhile Profitability and Debt to Equity Ratio (DER) has positive effect on dividend policy. Based on the result of this study, when the company want to pay dividends, accordingly, they should pay attention to the profitability, this is because companies that have high profitability will share high dividends to shareholders. Keywords : Agency Cost, Profitability, Debt to Equity Rati (DER), Dividend Policy